A Stakeholder Model for Interorganizational Information Systems - Ballejos, Luciana Cristina (2008)
Stakeholders constitute the principal source of requirements in the development of information systems. They therefore must be considered allover the process. In order to achieve success, they must be also modelled and then integrated with requirements, design and implementation models. Thus, a more complete perspective is added to traditional modelling. This work presents and describes a stakeholder model for interorganizational information systems, in order to incorporate a stakeholders-including approach to traditional modelling, focusing on interorganizational environments.